A desconstrução dos discursos de ódio na formação do sujeito reflexivo na escola - Maria Tereza Rocha de Oliveira (2020)
This research was conducted to help students, in the final years of elementary school, develop basic argumentative skills. In this context, even during the investigative process, in the initial phase of this research, it was noticed that, beyond the gaps in the argumentative capacity, there were other even more serious challenges: hate speeches, lack of empathy and the absence of ethical attitudes., that were frequently diagnosed in classroom teaching practices. It was realized that those discourses were mainly targeted to black people, which highlighted the existence of discriminative discursive voices against them in the classroom, naturally said, as something introjected, preventing the reflection on the negative social effects of such discrimination on the life of the other. Thus, beyond the objective of developing the student's argumentative skills, it was needed that these abilities were based on the deconstruction of the hate speech. This research was developed with students of the ninth year of Elementary School, at the State School Tiradentes, located inside a military area of the Air Force, in the city of Lagoa Santa, Minas Gerais. For the elaboration of didactic interventions and data analysis, this research had as theoretical basis the following thinkers and researchers: Bakhtin (2003), Amossy(2016), Orlandi (2009), Rojo (2015), Charaudeau (2006 and 2016), Fiorin(2015), among others. This intervention research is a qualitative approach that seeks to solve a real problem in the teaching of the mother language, which is to develop in the students a more critical view of the power of language, and how it can build, but also destroy, considering, for example, hate speeches against blacks. With the aim of developing, not only indispensable discursive abilities and skills, but also and mainly awakening in students the formation of reflective thinking, ethical attitudes, and socio-emotional development by practicing empathy in dealing with each other, six workshops were held, strategically planned for this purpose. The methodology used contributed both to a progression in the reading and production of more coherent, persuasive, and authorial texts, as well as to foster the protagonism of students as subjects who reflect on their practices and promote attitudes changes. It was observed, during the development, as well as in the culmination of the research, that the main and specific objectives were largely achieved, in spite of the resistance of some in mentioning this subject.